2017
DOI: 10.18632/aging.101248
|View full text |Cite
|
Sign up to set email alerts
|

Aged induced pluripotent stem cell (iPSCs) as a new cellular model for studying premature aging

Abstract: Nuclear integrity and mechanical stability of the nuclear envelope (NE) are conferred by the nuclear lamina, a meshwork of intermediate filaments composed of A- and B-type lamins, supporting the inner nuclear membrane and playing a pivotal role in chromatin organization and epigenetic regulation. During cell senescence, nuclear alterations also involving NE architecture are widely described. In the present study, we utilized induced pluripotent stem cells (iPSCs) upon prolonged in vitro culture as a model to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 46 publications
3
31
0
Order By: Relevance
“…However, in our conditions, we observed that SaOS2 cells accumulates nuclear abnormalities and, at the same time, they are low proliferative cells. In support of this, we found in the literature some papers in which nuclear abnormalities are found in low proliferative cells: a high amount of nuclear dysmorphisms have been described in aged, low proliferative iPSC cells and in senescent cells [8,54]. In addition to increased nucleoskeletal dysmorphisms, osteosarcoma cell lines have significant alteration of A-type and B-type lamins, as well as of emerin expression in comparison to normal osteoblasts.…”
Section: Discussionmentioning
confidence: 53%
“…However, in our conditions, we observed that SaOS2 cells accumulates nuclear abnormalities and, at the same time, they are low proliferative cells. In support of this, we found in the literature some papers in which nuclear abnormalities are found in low proliferative cells: a high amount of nuclear dysmorphisms have been described in aged, low proliferative iPSC cells and in senescent cells [8,54]. In addition to increased nucleoskeletal dysmorphisms, osteosarcoma cell lines have significant alteration of A-type and B-type lamins, as well as of emerin expression in comparison to normal osteoblasts.…”
Section: Discussionmentioning
confidence: 53%
“…While y-iPSCs appear as well-organized colonies with regular margins, aged iPSCs display progressive loss of their ability to form colonies, and cells are found in small groups with irregular shapes (ma-iPSCs) or isolated (a-iPSCs) (Figure 1 ). Noteworthy, aging iPSCs maintain their pluripotency features, as already demonstrated [ 8 ]. Based on these observations, we explored ultrastructural features of iPSCs using a Dualbeam FIB/SEM Helios Nanolab microscope (FEI, Hillsboro, USA), an instrument that combines an electron beam (SEM column) with a focused gallium ion beam (FIB column), oriented at 52°, and focusing on the same area of the specimen.…”
Section: Resultsmentioning
confidence: 68%
“…For this reason, we performed ultrastructural studies focusing on the nuclear and cytoplasmic features during in vitro maintenance in aerobic environment. The current concept that iPSCs can be indefinitely maintained in culture has been recently challenged by studies on the epigenetic status, the nucleoskeleton, and the mito-chondrial functionality in long-term cultured iPSCs (up to one year) in incubators with O 2 21%; CO 2 5%, which however do not mimic the physiological stem cell niche [ 6 - 8 ]. Moreover, tumorigenic potential is demonstrably increased in “aged” iPSCs [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to rejuvenation of neurons from iPSCs, our results also raise concerns on using iPSCs to model age-dependent neurodegenerations. Such concerns have already drawn attention, as strategies are emerging to induce aging-like features in iPSC-derived cells, for example, by telomerase manipulation ( Vera et al, 2016 ), progerin treatment ( Miller et al, 2013 ), or prolonged culture ( Petrini et al, 2017 ). Clearly, a cell culture system maintaining aging features such as our directly reprogrammed MNs will greatly facilitate our understanding of neurodegeneration and therapeutic identification and validation.…”
Section: Discussionmentioning
confidence: 99%